PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP KEPUASAN PASIEN ANTE NATAL CARE DI PMB SRI SUPIYATI TANGERANG BANTEN TAHUN 2022 - Sri Wahyuningsih (Universitas Muhammadiyah Tangerang, 2025)
THE EFFECT OF THERAPEUTIC COMMUNICATION ON ANTE NATAL CARE SATISFACTION PATIENT AT PMB SRI SUPIYATI TANGERANG BANTEN IN 2022 ABSTRACTBackground: Based on data on ANC services at PMB Sri Supiyati, it shows that the number of visits has decreased from 2020 by 52% to 38% in 2021. Meanwhile, based on the results of the researchers' initial interviews with 15 ANC patients, there were 40% who said they were not satisfied with the service because the communication was not appropriate during the consultation and the attitude of the midwives was not friendly.Research Objectives: To analyze the effect of therapeutic communication on ANC patient satisfaction at PMB Sri Supiyati Tangerang Banten in 2022. Research method: Using a type of quantitative research with a Cross Sectional design. The population of this study were all ANC patients. The sample size is 88 respondents with a sampling technique that is non probability with accidental sampling. Data analysis used univariate analysis and bivariate analysis used chi square. Research results: Indicates that there is a significant effect between therapeutic communication and ANC patient satisfaction at PMB Sri Supiyati Tangerang Banten in 2022. The results of statistical analysis using the Chi Square Test with a confidence level of 95% obtained a P-Value = 0.000 smaller than the P-Value (0.05) which means that the P-Value < α (0.05) in other words indicates a significant relationship. So that there is an effect of therapeutic communication on ANC patient satisfaction at PMB Sri Supiyati Tangerang Banten in 2022.Conclusions and Suggestions: In this study there is an influence between good therapeutic communication on ANC patient satisfaction, so it is hoped that midwives will maintain and improve good therapeutic communication in ANC services because it is an important asset to improve the progress of PMB and always conduct periodic evaluations of patient satisfaction. Reading List: 25 (Year 2013 – 2021)Keywords: Therapeutic Communication, Patient Satisfaction, Antenatal Care.